2004
DOI: 10.1254/jphs.94.325
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin Suppresses Lipopolysaccharide-Induced Cyclooxygenase-2 Expression by Inhibiting Activator Protein 1 and Nuclear Factor κB Bindings in BV2 Microglial Cells

Abstract: Inflammation is a significant component of chronic neurodegenerative diseases. Cyclooxygenase-2 (COX-2) is expressed in activated microglial cells and appears to be an important source of prostaglandins during inflammatory conditions. To investigate the effect of curcumin on COX-2 gene expression in microglial cells, we treated lipopolysaccharide (LPS)-challenged BV2 microglial cells with various concentrations of curcumin. Curcumin significantly inhibited LPS-mediated induction of COX-2 expression in both mRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
104
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 161 publications
(112 citation statements)
references
References 17 publications
6
104
2
Order By: Relevance
“…Accumulating evidences suggest that curcumin inhibits the expression of COX-2 in several experimental models (Zhang et al, 1999;Chun et al, 2003;Surh, 2003;Kang et al, 2004). Consistent with these, through the present study, we have demonstrated that curcumin also effectively inhibits the expressions of COX-2 mRNA and protein induced by UVB irradiation in a human keratinocyte cell line HaCaT, which seems to be, to our knowledge, the first report.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Accumulating evidences suggest that curcumin inhibits the expression of COX-2 in several experimental models (Zhang et al, 1999;Chun et al, 2003;Surh, 2003;Kang et al, 2004). Consistent with these, through the present study, we have demonstrated that curcumin also effectively inhibits the expressions of COX-2 mRNA and protein induced by UVB irradiation in a human keratinocyte cell line HaCaT, which seems to be, to our knowledge, the first report.…”
Section: Discussionsupporting
confidence: 91%
“…Curcumin is known to exert its anti-inflammatory action in various cell lines through inhibition of COX-2 expression (Chun et al, 2003;Kang et al, 2004). Thus, it is important to develop an efficient strategy using curcumin to down-regulate the expression of COX-2 in UVB-irradiated skin (Wolf et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Microglial cells are important players in immune and inflammatory responses in the CNS (Nam et al 2010), and their activation is implicated in several chronic neurodegenerative diseases, such as Alzheimer's disease (AD), Parkinson's disease (PD) and brain ischemia (Kang et al 2004). Activated microglial cells promote neuronal injury via the production of pro-inflammatory molecules such as the cytokines, tumor necrosis factor (TNF) α and interleukin (IL)-1β, and other cytotoxic molecules, such as reactive oxygen species (ROS) (Dheen et al 2007).…”
Section: Introductionmentioning
confidence: 99%